Challenges for service providers in community forestry governance: A case study of a community forest users group in Parbat, Nepal - Paudel, A; Vogel, S (Banko Janakari, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> This study was carried out in Bhodkhore Community Forest Users Group in Parbat district, Nepal with the overall objective to develop a clearer understanding of the challenges for service providers while working towards improving the Community Forestry governance. The primary data were collected through personal interviews, group discussions, key informant interviews and direct observations using a series of questionnaires and check lists. Similarly, the secondary data were gathered from reports and records from Community Forestry User Group and service providers, and from relevant scientific literature. The data were analyzed using qualitative and quantitative tools. The results show that the existing challenges for service providers mainly include financial resource management, time management and inadequate technical support for forest management. Key words: Community Forestry, Governance, Service Providers, Challenges doi: 10.3126/banko.v18i2.2169 Banko Janakari, Vol. 18, No. 2, 18-24